Pengaruh Teknologi Informasi dan Dukungan Manajemen Puncak Terhadap Kualitas Sistem Informasi Akuntansi: (Studi Pada Badan Keuangan Provinsi Gorontalo) - Risma Hayati K. Haruna; Gaffar Gaffar; Usman Usman (Al-Buhuts, 2024)
The purpose of this study is to find out the Effect of Information Technology and Peak Management Support on the Quality of Accounting Information System (Case Study on the Financial Agency of Gorontalo Province). This study used quantitative research methods. The data source used in this study was primary data obtained from the questionnaire distributed to 68 respondents in this study in the form of employees of the Gorontalo Provincial Finance Agency who were directly involved in regional financial management through the Regional Government Information System (SIPD) using Purposive sampling. The data analysis technique in this study is a descriptive quantitative analysis using statistical tests, statistical f tests, and a coefficient determination test (Adjusted R Square) using IBM SPS 26 for windows. The results of this study show that information technology has a positive and significant effect on the quality of the accounting information system and peak management support has a positive and significant effect on the quality of the accounting information system and simultaneous peak management information technology and support. With a determinant of 20.6% while 79.4% of the remaining 79.4% were explained by other variables not examined in this study